Observational Requirements for Long-Term Monitoring of the Global Mean Sea Level and Its Components Over the Altimetry Era - Cazenave, Anny; Hamlington, Ben; Horwath, Martin; Barletta, Valentina R.; Benveniste, Jérôme; Chambers, Don; Döll, Petra; Hogg, Anna E.; Legeais, Jean François; Merrifield, Mark; Meyssignac, Benoit; Mitchum, Garry; et al. (Frontiers in Marine Science, 2019)
Present-day global mean sea level evolution results from ocean thermal expansion as well as changes of glaciers and ice sheets mass, and in terrestrial water storage. It is considered as an integrator of changes occurring in the climate system in response to unforced climate variability as well as natural and anthropogenic forcing factors. Monitoring the global mean sea level allows detecting changes (e.g., in trend or acceleration) in one or more components. Closure of the sea level budget implies that the observed sea level changes equal the sum of observed contributions. Mis-closure of these balances indicates errors in some of the components or contributions from missing or un-assessed elements in the budget. Since the launch of TOPEX/Poseidon in 1992, we now have a precise 26-year continuous record of sea level change that has allowed major advances in our understanding of how the Earth is responding to climate change. Two more recent developments fundamentally improved our capability to study the causes of sea level change: the launch of the GRACE satellite gravity mission and the establishment of the Argo network of profiling floats. GRACE has given us the ability to monitor mass redistributions anywhere on Earth, in particular land ice mass variations, and changes in terrestrial water storage and in ocean mass. The Argo network provides a means of monitoring the contribution of thermosteric sea level changes due to the warming of the oceans. Together, satellite altimetry, space gravity, and Argo measurements provide unprecedented insight into the magnitude, spatial variability, and causes of present-day sea level change. With this observational network that has continued to improve in recent years, we are now in a position to address many outstanding questions that are important to planning for future sea level rise. Here, we detail the network for observing sea level and its components, underscore the importance of these observations, and emphasize the need to maintain current systems, improve their sensors, and supplement the observational network where gaps in our knowledge remain.